Qur'anic Condemnation of Feminicide: A Feminist-Hermeneutical Analysis of Verses Addressing Gender-Based Violence - Fitri Meliani; Abdul Aziz; M. Rasyidul Fikri (UIN Sunan Gunung Djati Bandung, 2026)
The rising phenomenon of femicide across various countries, including Indonesia, reflects a humanitarian crisis rooted in patriarchal social structures and gender-biased religious interpretations. This study is driven by the need to connect feminist readings of Qur’anic verses with the real and urgent problem of gender-based violence, an issue that remains underexplored in Qur’anic exegesis. The research aims to explain the Qur’an’s condemnation of femicide and to examine how feminist exegesis interprets verses often used to legitimize the subordination of women. Employing a thematic (maudu‘i) method combined with historical, critical, and contextual approaches, the analysis draws on Fazlur Rahman’s Double Movement theory to uncover the Qur’an’s universal moral message and its relevance to contemporary social realities. The findings reveal that the Qur’an firmly rejects all forms of zulm (oppression) and affirms karamah insaniyyah (human dignity) as a foundational principle, making violence against women—including femicide—fundamentally incompatible with divine justice. Feminist interpretations of gender-related verses offer a more equitable, humanistic, and context-sensitive reading of the Qur’an, thereby reinforcing principles of equality and the protection of women’s lives. This study underscores the urgency of developing feminist exegesis as a transformative hermeneutical paradigm that strengthens the Qur’an’s commitment to social justice in contemporary discourse.